2020
DOI: 10.4081/ejtm.2020.9050
|View full text |Cite
|
Sign up to set email alerts
|

Percentile values of the standing broad jump in children and adolescence aged 6-18 years old

Abstract: The standing broad jump (SBJ) is a valid, reliable and feasible field-based test, which can evaluate explosive strength of the lower limbs and physical fitness. This study aimed to provide normative data for the SBJ for male and female children and adolescents and describe differences in performance between age groups and genders. A total number of 2140 children and adolescents, sampled in seven European nations have been included for analysis. The SBJ was performed to derive percentile values for gender and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Therefore, the reliability, validity evidence, and norm reference for lower body muscular power in this population need to establish to ensure that the data obtained are meaningful and the selection process is accurate as required. Even though Thomas, Petrigna, Tabacchi, Teixeira, Pajaujiene, Sturm, Sahin, Lopez, Pausic, Paoli, Alesi, & Bianco (2020) have come out with norm for SBJ, but the differences of age and population causes the validity and reliability can be questionable. Therefore, the purposes of this study are to establish reliability, validity evidence and develop a specific norm-referenced standard for lower body muscular power assessed by SBJ.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reliability, validity evidence, and norm reference for lower body muscular power in this population need to establish to ensure that the data obtained are meaningful and the selection process is accurate as required. Even though Thomas, Petrigna, Tabacchi, Teixeira, Pajaujiene, Sturm, Sahin, Lopez, Pausic, Paoli, Alesi, & Bianco (2020) have come out with norm for SBJ, but the differences of age and population causes the validity and reliability can be questionable. Therefore, the purposes of this study are to establish reliability, validity evidence and develop a specific norm-referenced standard for lower body muscular power assessed by SBJ.…”
Section: Introductionmentioning
confidence: 99%
“…Hartman et al (2015) reported similar results for children with severe ID when compared to those with mild or no ID. Lower limb strength was assessed using the standing broad jump which has previously been reported to be a valid, reliable and feasible field‐based test to assess explosive strength (Thomas et al, 2020), results would indicate that children with ASD require further developmental assistance in lower limb strength and acceleration, unlike their ND peers. The results of the current study would suggest that a more practical method to estimate potential deficits in fitness measures in children with ASD would be to compare the child's fitness results to the normative values reported for ND children within the present study.…”
Section: Discussionmentioning
confidence: 99%
“…To aid with interpretation of maximal SLJ distance, age- and sex-specific percentile rank normative values were calculated for each participant using American [ 18 ] and European [ 19 , 20 ] SLJ norms. The American norms, while most recent from within the country, were somewhat antiquated.…”
Section: Methodsmentioning
confidence: 99%
“…Further, due to limited investigation, uncertainties remain surrounding factors that may influence and/or be predictive of SLJ performance in youth with VI (e.g., age, height, degree of vision). Insights into such information would be valuable as discrepancies may be uncovered when compared to what has traditionally been found in youth without VI (e.g., being older in age and/or being a boy typically leads to increased SLJ distance [ 18 , 19 , 20 ]). Such findings would empirically inform what factors may (or may not) be influencing SLJ performance in youth in VI.…”
Section: Introductionmentioning
confidence: 99%